ANALISE MORFOLOGICA DE 'SPINA MENTALIS' DE MANDIBULAS HUMANAS ADULTAS DE BRASILEIROS BRANCOS E NEGROS - Oda, L. S.; Iyomasa, M. M.; II-Sei Watanabe, (My University, 1977)
This study was carried out to verify the morphology of the spina mentalis. We observed 275 human adult mandibles of both sexes and ethnic groups. An analysis of the results allows the following conclusions. The spina mentalis exists in 90.04% ±1.8 of the mandibles of Whites and Negroes. The typical form with four tubercles, as described by some authors, is rarely found. In most cases it is characterized by the presence of: two upper tubercles (27.27%±7.2), two superior tubercles and one inferior (24.72%±6.7), and one elongated median tubercle (24.0%±6.6); The forms and volumes of the tubercles are very irregular and seem not to depend on age, sex or ethnic group. The spina was absent in 9.8%±3.2 of the cases, especially in mandibles of White teethless individuals. An hypertrophic spina mentalis, generally formed at the expense of the upper tubercle, was observed in only 1.45%±0.5 of the cases.
Morphologic analysis of the 'spina mentalis' in adult mandibles of Brazilian Whites and Negroes
Keywords: bone; ethnic or racial aspects; geographic distribution; mental spine; normal human; Brazil; Caucasoid Race; Comparative Study; Female; Human; Male; Mandible; Negroid Race; Sex Factors